2006
DOI: 10.1038/ng1789
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide analysis of mammalian promoter architecture and evolution

Abstract: Mammalian promoters can be separated into two classes, conserved TATA box-enriched promoters, which initiate at a well-defined site, and more plastic, broad and evolvable CpG-rich promoters. We have sequenced tags corresponding to several hundred thousand transcription start sites (TSSs) in the mouse and human genomes, allowing precise analysis of the sequence architecture and evolution of distinct promoter classes. Different tissues and families of genes differentially use distinct types of promoters. Our tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

160
1,390
5
10

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,255 publications
(1,592 citation statements)
references
References 40 publications
160
1,390
5
10
Order By: Relevance
“…This idea is also supported by a previous study by Kruse et al ., who showed reduction of mir-1176 and mir-1177 upon treatment with α-amanitin [30] and is in agreement with the situation in animals and plants where most pri-miRNAs are transcribed by RNA Pol II [46]. Furthermore, mammalian RNA Pol II transcripts preferentially start with a purine preceded by a pyrimidine [53,62], which complies with the T and G at position −1 and +1, respectively, seen for the pri-miRNA associated motif in D. discoideum . This purine-pyrimidine preference was also reported for miRNA genes in Arabidopsis [5].…”
Section: Resultssupporting
confidence: 62%
“…This idea is also supported by a previous study by Kruse et al ., who showed reduction of mir-1176 and mir-1177 upon treatment with α-amanitin [30] and is in agreement with the situation in animals and plants where most pri-miRNAs are transcribed by RNA Pol II [46]. Furthermore, mammalian RNA Pol II transcripts preferentially start with a purine preceded by a pyrimidine [53,62], which complies with the T and G at position −1 and +1, respectively, seen for the pri-miRNA associated motif in D. discoideum . This purine-pyrimidine preference was also reported for miRNA genes in Arabidopsis [5].…”
Section: Resultssupporting
confidence: 62%
“…The molecular mechanisms and governing signals involved remain undiscovered. Carninci et al (2006) reported recently that, in a genome-wide scale, multiple promoters, belonging to different classes, could be located within single-gene loci, also including their exons. In this combinatorial vision of the transcriptome, Ron's complex transcriptional regulation should not be considered an isolated case.…”
Section: Discussionmentioning
confidence: 99%
“…Another intriguing possibility is that alternative promoter usage leading to inclusion or exclusion of a splicing event upstream of an ALREX element can allow switching between the two export pathways, thereby regulating subsequent mRNA expression. Expressed sequence tags (ESTs), cap analysis of gene expression (CAGE), and RNASeq data indicate that alternate promoter use is widespread in higher eukaryotes; 30-50% of all human and mouse genes have been reported to contain alternate promoters [31,32]. To a smaller extent, 5UIs can be alternatively retained in the mature mRNA, rather than spliced out [33,34].…”
Section: Splicing Directs Mrnp Formationmentioning
confidence: 99%